Metabolismo antioxidativo, biotransformação hepática e alterações histológicas de matrinxã (Brycon amazonicus, SPIX & AGASSIZ, 1829, CHARACIDAE) exposto ao fenol - Avilez, Ive Marchioni (2008)
Pollution is nowadays a problem that affects all environments, including the freshwater and the species living in there. Among them, under the ecotoxicological point of view, fish are a relevant group and the biggest among vertebrates. Phenol is an exogenous chemical usually present in concentrations higher than those allowed by law. Phenol is an organic lipophilic xenobiotic that cause toxic effects even at low concentrations and its presence in freshwater results from discharge of industrial efffluents. The aim of the present study was to determine the phenol effects 1) in the liver and red blood cells antioxidant metabolism, 2) in the liver biotransformation (phase I and II), 3) in the brain acetylcholinesterase plus recovery of 1 and 2 weeks and 4) in gills, liver and kidney, under the histopathological point of view, in matrinxã, Brycon amazonicus, a freshwater teleost from Amazon basin, which is being widely cultivated in Sao Paulo state. For such, three assays were done. Firstly, the phenol LC50 was determined for 96 hours. Second, the exposition to phenol was carried out for 96 h to determine its effects on gills, liver and kidney. At last, an experiment of exposure for 96 h, followed by recovery for one and two weeks, was carried out to determine its antioxidant effects on the liver and on the red blood cell metabolism (vitamin C, SOD, CAT, GPx, GSH and G6PDH); on two liver biotransformation phase I (EROD and ECOD) and phase II activities (UDPGT and GST) and brain acetylcholinesterase activity. The LC50 to phenol was 17, 40 mg/L, showing that matrinxã is a very sensitive species to phenol. From this, the phenol concentration used in all experiments was 2 mg/L. Histopathology observations showed that phenol affected harder the gills than liver and kidney, causing apical and total fusion of the secondary lamella plus blood congestion and sub epithelial edema. In the liver diameter increase of the sinusoidal capillaries and blood stasis was observed. In the kidney, phenol caused an increase of the space between glomerulus and capsule. A hematocrit increase was observed in fish exposed and recovery for one week. These results, associated to gill lesions, suggested that matrinxã endured a reduction in oxygen absorption. Erythrocyte antioxidant metabolism did not suggest that matrinxã exposed to phenol was under oxidative stress. Only G6PDH activity was increased during exposure, while CAT activity was decreased in matrinxã s erythrocytes. Also, oxidative stress was not observed after recovery. The antioxidant metabolism in liver was not affected after exposure, but after recovery, as it is suggested by the increase of GPx activity after first week of recovery followed by its decrease after second week. Hepatic G6PDH also decreases after the second week. These results corroborated the hepatic biotransformation data, which was increasing in the EROD and ECOD activities. The occurrence of oxidative stress only after the recovery may be ascribed to the increase in the hepatic biotransformation enzymes of the phase I, wherein the ERO production occurs. Moreover, phenol might have an inhibitory effect on phase II enzymes after phenol exposure, as suggested by UDPGT and GST activities decreases. Phenol was capable of inhibiting UDPGT activity in vitro, an effect not observed with GST activity. An inhibition of EROD and ECOD activities should be happened after exposition. The brain AChE activity was also inhibited after phenol exposure, regaining the control values after recovery. However, the vitamin C concentration increased after exposure and recovery, while a persistent decrease was observed in the liver after exposure and recovery. These results demonstrated phenol toxicity to matrinxa and the need of limit matrinxã exposure to this xenobiotic.